Carbapenem-Resistant Enterobacteriaceae Resistant Only to Ertapenem: An Epidemiologically Distinct Cohort, Atlanta, 2016–2018. (October 2020) - Bower, Chris; Adelman, Max; Howard-Anderson, Jessica; Ansari, Uzma; Lutgring, Joseph; Tiga, Gebre; Jacob, Jesse
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE), particularly carbapenemase-producing (CP) CRE, pose a major public health threat. In 2016, the phenotypic definition of CRE expanded to include ertapenem resistance to improve sensitivity for detecting CP-CRE. We compared characteristics of CRE resistant to ertapenem only (CRE-EO) to CRE resistant to ≥1 other carbapenem (CRE-O). Methods: The Georgia Emerging Infections Program performs active, population-based CRE surveillance in metropolitan Atlanta. CRE cases were defined as any Escherichia coli, Klebsiella pneumoniae, K. oxytoca, K. variicola, Enterobacter cloacae complex, or Enterobacter aerogenes resistant to ≥1 carbapenem by the clinical laboratory and isolated from urine or a sterile site between 2016 and 2018. Data were extracted from retrospective chart review and 90-day mortality from Georgia vital statistics for 2016–2017. Polymerase chain reaction (PCR) for carbapenemase genes was performed on a convenience sample of isolates by the CDC or Georgia Public Health Laboratory. We compared characteristics of CRE-EO cases to CRE-O cases using χ 2 tests or t tests. Results: Among 927 CRE isolates, 553 (60%) were CRE-EO. CRE-EO were less frequently isolated from blood (5% vs 12%; P < .01) and less commonly K. pneumoniae (21% vs 58%; P < .01) than CRE-O. CRE-EO cases were more often women (65% vs 50%; P < .01), had a lower Charlson comorbidity index (mean ± SD, 2.4±2.3 vs 3.0±2.6; P < .01), and were less commonly at a long-term care facility (24% vs 31%) or hospital (15% vs 21%; P < .01) in the 4 days prior to the CRE culture. CRE-EO were more susceptible to all antibiotics tested at the clinical laboratory ( P < .01) except for tigecycline ( P = 1.0) (Table 1). Of the 300 (32%) isolates tested for carbapenemase genes, 98 (33%) were positive (7% CRE-EO vs 62% CRE-O; P < .01). Of the CP isolates, we identified bla KPC in 93 cases (95%), bla NDM in 3 cases (3%), bla OXA-48-like in 2 cases (2%). CRE-EO cases had lower 90-day mortality (13% vs 21%; P < .01). Conclusions: CRE-EO are epidemiologically distinct from CRE-O and are less likely to harbor carbapenemase genes. CRE-EO may require less intensive infection prevention interventions and have more therapeutic options. Funding: None Disclosures: None